Low-carbon recycled aluminum alloy plate and preparation method thereof

By melting the sheet material in the carrier aluminum liquid and removing the oxide film residue, the problem of oxide film dispersion in recycled aluminum alloy sheets is solved, the forming stability and performance consistency of the sheets are improved, and the amount of primary aluminum and intermediate steps are reduced.

CN122648757BActive Publication Date: 2026-11-06江苏汇联铝业有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611164183.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-11-06
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

In the current production of recycled aluminum alloy sheets, the oxide film formed on the surface of the aluminum alloy sheet recycled material during processing and heating is easily broken and dispersed into the molten aluminum, resulting in inclusions and cascading during casting and rolling, which affects the bending and forming stability of the sheet and the consistency of its performance in the width direction.

Method used

The method of melting thin sheet material in carrier aluminum liquid involves forming carrier aluminum liquid in a melting furnace and stopping forced circulation and mechanical stirring, so that the metal matrix in the thin sheet material melts and the oxide film residue remains in the carrier component. Then the carrier component is removed and the aluminum liquid is homogenized and the composition is adjusted to obtain low carbon recycled aluminum alloy sheet.

Benefits of technology

This method achieves separation of the oxide film from the metal substrate, reduces the dispersion of the oxide film in the molten aluminum, improves the forming stability and performance consistency of recycled aluminum alloy sheets, and reduces the amount of primary aluminum used and the intermediate remelting process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122648757B_ABST
    Figure CN122648757B_ABST
Patent Text Reader

Abstract

This invention relates to the field of recycled aluminum alloy sheet preparation technology, and discloses a low-carbon recycled aluminum alloy sheet and its preparation method. The method involves stacking aluminum alloy sheet recycled material to form a sheet assembly with interconnected gaps, and then melting it in a carrier molten aluminum solution while the forced circulation and mechanical stirring are stopped. This allows the sheet metal matrix to melt and enter the main molten pool. The oxide film residue is concentrated in the carrier component. Before starting circulation or stirring, the residue is removed. Then, the molten aluminum solution in the main molten pool is homogenized, purified, and cast in the same furnace. This method can reduce the breakage of the oxide film and its entrapment in the molten aluminum solution and the formation of inclusions in the sheet, thereby improving the bending stability and cross-sectional performance consistency of the recycled aluminum alloy sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of recycled aluminum alloy sheet preparation technology, and in particular to a low-carbon recycled aluminum alloy sheet and its preparation method. Background Technology

[0002] The production of aluminum alloy sheets generates scrap materials such as trimmed edges, stamping offcuts, and substandard sheets, which are then recycled. Reusing these waste materials in sheet production reduces primary aluminum consumption and energy consumption from repeated processing, a common way to lower carbon emissions from aluminum alloy sheet production. Existing aluminum alloy sheets have an oxide film formed on their surface during processing, storage, and repeated heating.

[0003] Existing technologies have improved recycled aluminum production in various ways. For example, Chinese patent CN102140579B discloses a low-temperature immersion melting process for recycled aluminum, which involves sorting scrap aluminum by type and thickness, retaining the molten aluminum in the furnace, and performing low-temperature immersion melting to reduce oxidation loss of scrap aluminum on the liquid surface and increase metal yield. In addition, another Chinese invention patent CN118957369B discloses a 5xxx aluminum alloy, its preparation method, and its application. By adjusting the content of elements such as Mg, Mn, Fe, Cr, Sr, and Mo, and controlling the size and quantity of Fe-containing phases, the impurity tolerance and formability of the recycled 5xxx aluminum alloy are improved.

[0004] Existing technologies can improve the melting efficiency, alloy composition, and intermetallic compound state of scrap, but the non-metallic inclusions formed by the oxide film inherent in aluminum alloy scrap are still difficult to resolve through composition adjustment. Chunfa Huang et al., in their paper "Evolution Behavior of the Surface Oxide Film of Al Alloy Scraps in the Melt" published in *Metals*, demonstrated that the oxide film on the surface of scrap aluminum undergoes morphological changes depending on the melt composition and residence conditions after entering the molten aluminum. 5083 scrap can retain a large sheet-like oxide film in Mg-containing melts, while under other melt conditions, it can further transform into smaller oxides. In their article "High-temperature heat treatment attenuating the influence of micron-sized inclusions on the microstructure and properties of recycled Al-Zn-Mg-Cu alloysheet" published in the Journal of Materials Research and Technology, Sen Du et al. pointed out that micron-sized inclusions in recycled aluminum melt are difficult to completely remove through conventional purification methods, and may still cause local strain concentration after rolling. Existing processes still face the problem of balancing the melt uniformity of thin sheet waste with the local forming reliability of the resulting sheet. Summary of the Invention

[0005] The technical problem to be solved by the present invention is that in the production of recycled aluminum alloy sheets, the surface of aluminum alloy sheet remelting material usually has an oxide film formed during processing, storage and heating. The oxide film is easily broken, rolled into and dispersed into the aluminum liquid under forced circulation or mechanical stirring, and forms an inclusion series along the rolling direction during subsequent casting and rolling processes, thereby affecting the bending and forming stability and width direction performance consistency of the recycled aluminum alloy sheet.

[0006] To achieve the above objectives, this application adopts the following technical solution: a low-carbon recycled aluminum alloy sheet and its preparation method, comprising the following steps:

[0007] S1: Stack aluminum alloy sheet remelting material to form sheet material group, so that there are connecting gaps between the sheets for the carrier aluminum liquid to enter and the liquid metal to flow out;

[0008] S2: A carrier aluminum liquid is formed in the smelting furnace. The Mg mass percentage in the carrier aluminum liquid is 2.5%-3.5%. Forced circulation and mechanical stirring are stopped before the carrier aluminum liquid is added to the sheet material group.

[0009] S3: The sheet material group is placed in a support component with a liquid permeation opening and immersed in the carrier aluminum liquid. Under the state of forced circulation and mechanical stirring stopped, the metal matrix in the sheet material group is melted. The molten liquid metal formed enters the main molten pool through the connecting gap and the liquid permeation opening. The residue of the enriched oxide film remains in the support component.

[0010] S4: Before starting forced circulation or mechanical stirring, remove the supporting component along with the residue of the enriched oxide film from the molten aluminum;

[0011] S5: After the residue of the enriched oxide film is removed, start forced circulation or mechanical stirring to homogenize the aluminum liquid in the main molten pool, and adjust the composition, degas and filter the aluminum liquid to obtain purified aluminum liquid.

[0012] S6: The purified aluminum liquid is cast into rolled slabs in the same furnace. The rolled slabs are then homogenized, hot-rolled, cold-rolled and annealed to obtain low-carbon recycled aluminum alloy sheets.

[0013] Preferably, in S1, the aluminum alloy sheet remelting material is sheet-like or strip-like remelting material generated during the edge trimming, slitting, punching, or cutting process of aluminum alloy sheet and strip, with a thickness of 0.20-2.00 mm. After cleaning and drying, the aluminum alloy sheet remelting material has a moisture content of no more than 0.20% and a surface oil content of no more than 0.30%.

[0014] Preferably, in S1, the sheet material group is formed by interleaving and compacting recycled aluminum alloy sheets, and the apparent density of the sheet material group is 0.35-0.90 g / cm³. 3 Furthermore, gaps are maintained between the thin sheets to allow for interconnection.

[0015] Preferably, in S1, the cleaned and dried aluminum alloy sheet remelting material is preheated at 150-300°C for 20-60 minutes, and then the preheated aluminum alloy sheet remelting material is stacked to form the sheet material group.

[0016] Preferably, in step S2, the carrier aluminum liquid is formed by melting block aluminum alloy recycled material and primary aluminum in a smelting furnace, and the block aluminum alloy recycled material and the low-carbon recycled aluminum alloy sheet to be prepared belong to the same aluminum alloy series.

[0017] Preferably, in S3, the supporting component is an aluminum-resistant liquid support frame. The aluminum-resistant liquid support frame is provided with liquid permeation openings on its side and bottom. The liquid permeation openings allow the carrier aluminum liquid to enter and the molten liquid metal to flow out. The enriched oxide film residue in the form of flakes, films, flocculents or agglomerates remains in the aluminum-resistant liquid support frame.

[0018] Preferably, in step S3, the sheet material is immersed in the carrier aluminum liquid in batches, and the mass of each batch of aluminum alloy sheet remelting material is 5%-15% of the total mass of aluminum raw materials used to prepare the low carbon recycled aluminum alloy sheet; the sheet material is treated in the carrier aluminum liquid at a temperature of 700-735℃ for 8-25 minutes, and the carrier component is not subjected to reciprocating impact or flipping during the treatment.

[0019] Preferably, in S4, after each batch of sheet material is fully melted, the aluminum-resistant liquid support frame, along with the residue of the enriched oxide film, is moved to the top of the main molten pool for 2-8 minutes to drain.

[0020] Preferably, in step S5, after all batches of enriched oxide film residues have been removed, the main molten aluminum pool is mechanically stirred and homogenized at 700-730℃, with a stirring speed of 60-180 r / min and a homogenization time of 3-15 min.

[0021] A low-carbon recycled aluminum alloy sheet, wherein the low-carbon recycled aluminum alloy sheet is composed of 50 parts aluminum alloy sheet remelting material, 40 parts block aluminum alloy remelting material, and 10 parts primary aluminum, based on a total mass of 100 parts of aluminum raw materials.

[0022] Preferably, the thickness of the aluminum alloy sheet remelting material is 0.20-2.00 mm, the block aluminum alloy remelting material is aluminum alloy thick plate cut-off, slab cut-off, scrap plate or other clean aluminum alloy remelting material with block shape, and the primary aluminum is industrial pure aluminum ingot or industrial pure aluminum liquid with an aluminum content of not less than 99.70%.

[0023] The technical effects and advantages of this invention are as follows: By forming aluminum alloy sheet remelting material into sheet batches and allowing them to fully melt in the carrier molten aluminum while the circulating pump and mechanical stirrer are off, the metal matrix in the sheet remelting material can melt and enter the main molten pool, while the oxide film formed on the sheet surface can be retained as residue within the carrier frame. This allows for the separation of molten metal and oxide film residue during the melting stage, reducing the likelihood of oxide film directly entering the main molten pool with the molten metal. Furthermore, by controlling the Mg content in the carrier molten aluminum, this invention makes it easier for the oxide film on the surface of the sheet remelting material to be retained as residue during the melting process. Combined with the stable retention of the oxide film by the carrier frame, this treatment method improves the concentration of oxide film residue, reduces its dispersion in the molten aluminum, increases the proportion of aluminum alloy remelting material used, and allows the purified molten aluminum to be directly cast into rolled slabs in the same heat, reducing the amount of primary aluminum used and the intermediate remelting process. Attached Figure Description

[0024] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings: Figure 1 A bar chart showing the oxide inclusion content in the aluminum melt obtained by each preparation method; Figure 2 A bar chart showing the width-direction range of A50 plates obtained by various preparation methods. Detailed Implementation

[0025] The present invention provides a low-carbon recycled aluminum alloy sheet. The total mass of aluminum raw materials used to prepare the low-carbon recycled aluminum alloy sheet is 100 parts. The aluminum raw materials include 30-75 parts of aluminum alloy sheet remelting material, 20-60 parts of block aluminum alloy remelting material, and 5-30 parts of primary aluminum. The amount of each component is selected within the above range and the total is 100 parts.

[0026] Specifically, the aluminum alloy sheet remelting material is sheet or strip metal material produced during the edge trimming, slitting, punching or cutting process of aluminum alloy sheet and strip, with a thickness of 0.20-2.00mm; aluminum alloy sheet remelting material is one of the main sources of recycled aluminum required for sheet metal production.

[0027] The blocky aluminum alloy remelting material is aluminum alloy thick plate cut-off, slab cut-off, scrap plate, or other clean aluminum alloy remelting material with blocky shape. The blocky aluminum alloy remelting material and the plate to be prepared belong to the same alloy series. The same alloy series means that the remelting material and the target plate belong to the same aluminum alloy series. The addition of the blocky aluminum alloy remelting material will not cause the alloy elements and impurity elements in the resulting plate to exceed the control range of the target plate.

[0028] The primary aluminum is industrial pure aluminum ingot or industrial pure aluminum liquid with an aluminum content of not less than 99.70%, used to replenish the metal content, and the content of impurity elements in the obtained aluminum liquid is adjusted according to the composition test results of the recycled aluminum alloy material.

[0029] This embodiment also provides a method for preparing low-carbon recycled aluminum alloy sheet, specifically including the following steps: S1. The aluminum alloy sheet remelting material is sorted, cleaned and dried. The processed aluminum alloy sheet remelting material is laid in an alternating manner and compacted to form sheet material groups, so that gaps are left between adjacent sheets for the aluminum liquid to enter and the molten metal to be discharged. S2. Retain the hot aluminum liquid from the previous furnace that has passed inspection in the main melting pool, melt some of the block aluminum alloy return material and primary aluminum to form carrier aluminum liquid, remove the slag on the surface of the carrier aluminum liquid, and stop the forced circulation and mechanical stirring in the melting furnace. S3. The sheet material is placed in batches into the carrier component containing the carrier aluminum liquid, so that the carrier aluminum liquid enters the sheet material and the metal matrix of the aluminum alloy sheet remelting material is melted without forced circulation and mechanical stirring; the molten liquid metal is discharged from the sheet material and the oxide film residue remains in the carrier component. S4. When the metal matrix in the sheet material group melts out and the residue with enriched oxide film is still concentrated in the bearing component, maintain the forced circulation and mechanical stirring in a stopped state, remove the residue from the aluminum liquid and drain it, so that the liquid metal carried by the residue returns to the main molten pool. S5. After the residue of the enriched oxide film is removed, start melt circulation or mechanical stirring, and add the remaining block aluminum alloy remelting material and primary aluminum according to the composition requirements of the target plate to homogenize and adjust the composition of the obtained aluminum liquid; then refine, degas and filter the aluminum liquid. S6. The purified aluminum liquid is directly cast into rolled slabs. The resulting rolled slabs are homogenized, hot-rolled, cold-rolled and annealed to obtain low-carbon recycled aluminum alloy sheets.

[0030] Specifically, in step S1, after the sorted aluminum alloy sheet remelting material is cleaned and dried, the moisture content is no higher than 0.20%, the surface oil content is no higher than 0.30%, and it is preheated at 150-300℃ for 20-60 minutes. The apparent density of the sheet material group is 0.35-0.90 g / cm³. 3 The thin sheets maintain interconnected gaps. The moisture content is determined by the drying and weighing method, and is expressed as the percentage of the mass difference before and after drying relative to the mass before drying; the surface oil content is determined by the solvent extraction and weighing method, and is expressed as the percentage of the mass of the extracted oily substance relative to the mass of the aluminum alloy sheet recycled material.

[0031] In step S2, the carrier aluminum liquid is the aluminum liquid retained after the previous batch has been tested for composition. The carrier aluminum liquid accounts for 20%-50% of the total mass of aluminum raw materials. The temperature before adding the sheet material group is 700-740℃. The carrier aluminum liquid is a magnesium-aluminum alloy liquid that is compatible with the composition of the target plate, wherein the Mg mass percentage is 2.5-3.5%.

[0032] In step S2, the carrier aluminum liquid is located in the main melting pool of the smelting furnace, and is used to immerse the sheet material group and receive the liquid metal formed by the melting of the sheet metal matrix; the main melting pool is the aluminum liquid area in the smelting furnace used to collect the carrier aluminum liquid and the molten metal of the sheet return material.

[0033] In step S3, the supporting component is an aluminum-resistant liquid support frame with liquid-permeable openings on the side and bottom. The liquid-permeable openings allow the carrier aluminum liquid and the molten liquid metal to pass through, and restrict flaky, flocculent or agglomerated residues from entering the main molten pool.

[0034] The support frame is used to contain and hold the sheet material group, and allows the carrier aluminum liquid to enter the sheet material group, while allowing the liquid metal formed after the sheet material is melted to return to the main molten pool. The oxide film residue on the surface of the sheet material remains in this area.

[0035] The bottom and sides of the support frame are provided with spaced strip-shaped liquid permeation openings. The effective width of the strip-shaped liquid permeation opening is 4mm, the length is 25mm, and the minimum distance between adjacent strip-shaped liquid permeation openings is 6mm.

[0036] Place the sheet material in batches into the support frame. The amount of sheet material added in each batch is 5%-15% of the total mass of aluminum raw materials. Treat the sheet material at 700-735℃ for 8-25 minutes. During the treatment, keep the circulation pump and mechanical agitator of the main molten pool closed and do not subject the sheet material to reciprocating impact, turning or stirring.

[0037] Under the above processing conditions, the carrier aluminum liquid enters the material group through the gaps between the sheets, the metal matrix of the sheet return material melts and flows into the main molten pool, and the residue of the enriched oxide film remains in the carrier frame.

[0038] In step S4, the liquid-permeable carrier component, along with the residue therein, is placed above the molten aluminum or at the molten aluminum return location to drain for 2-8 minutes, so that the liquid metal entrained therein returns to the main molten pool.

[0039] In step S5, after removing each batch of residues, the molten aluminum is stirred to homogenize it. The homogenization temperature is 700-730℃, the homogenization time is 3-15 min, and the stirring speed is 60-180 r / min.

[0040] In step S6, the homogenized and composition-adjusted molten aluminum is refined, degassed, and filtered, and then directly cast into rolled slabs in the same heat. The rolled slabs are then homogenized, hot-rolled, cold-rolled, and annealed to obtain low-carbon recycled aluminum alloy sheets. The specific operating conditions for refining, degassed, filtering, casting, and rolling are carried out according to the following embodiments.

[0041] The present invention will be described in detail below with reference to specific embodiments. It should be noted that these embodiments are only used to explain the present invention and do not constitute any limitation on the scope of protection of the present invention. Those skilled in the art can make adaptive adjustments to the embodiments based on their understanding of the technical solutions of the present invention, and these adjustments still fall within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment provides a low-carbon recycled aluminum alloy sheet. The aluminum alloy sheet is a low-carbon recycled aluminum alloy sheet with a thickness of 1.5 mm. The total mass of aluminum raw materials used to prepare the sheet is 100 parts, which includes 50 parts of aluminum alloy sheet remelting material, 40 parts of block aluminum alloy remelting material, and 10 parts of primary aluminum. The aluminum alloy sheet remelting material and the block aluminum alloy remelting material are both from the 5052 aluminum alloy sheet and strip production line. The primary aluminum is an industrial pure aluminum ingot with an aluminum content of not less than 99.70%.

[0044] This embodiment also provides a method for preparing low-carbon recycled aluminum alloy sheet, the specific steps of which are as follows: S1. Sorting of aluminum alloy sheet remelting material: Aluminum alloy sheets with a thickness of 0.50-0.80 mm are sorted and added to the remelting material for cleaning and drying. The moisture content is controlled at 0.08% and the surface oil content at 0.12%. The material is then preheated at 220℃ for 40 minutes. The preheated 50 portions of aluminum alloy sheet remelting material are divided into 5 batches of 10 portions each. Each batch of aluminum alloy sheet remelting material is then stacked and compacted to form sheet material groups. The apparent density of the sheet material groups is 0.58 g / cm³. 3 The thin sheets maintain interconnected gaps; S2. Add the block aluminum alloy recycled material into the melting furnace to melt it, remove the slag on the surface of the aluminum liquid, and form a carrier aluminum liquid; the Mg mass percentage in the carrier aluminum liquid is 3%, adjust the temperature of the carrier aluminum liquid to 720℃, and then turn off the circulating pump and mechanical stirrer of the melting furnace. S3. An aluminum-resistant liquid support frame with liquid-permeable openings on the sides and bottom is formed. The first batch of sheet materials is assembled into the support frame, and then the support frame is placed into the carrier aluminum liquid at a speed of 10 mm / s. The circulation pump and mechanical agitator are kept off, and the process is carried out at 720℃ for 13 minutes. During the process, the support frame is not subjected to reciprocating impact, rapid turning or forced stirring. The molten liquid metal is discharged into the main molten pool through the gaps between the sheets and the liquid-permeable openings of the support frame, and the residue of the enriched oxide film is left in the support frame. S4. After completing step S3, while the circulating pump and mechanical stirrer are still off, remove the support frame along with the residue from the molten aluminum and drain it above the main molten pool for 4 minutes, allowing the liquid metal carried by the residue to return to the main molten pool. After draining, collect the residue separately and do not return it to the current furnace. Process the remaining 4 batches of sheet metal in sequence according to steps S3 and S4. After each batch of sheet metal is processed and the residue is removed, restore the temperature of the molten aluminum in the pool to 720°C before processing the next batch of sheet metal. Do not start the circulating pump and mechanical stirrer until all the residue corresponding to the sheet metal is removed. S5. After all the sheet material groups have been processed and all batches of residues have been removed, add the reserved 10 portions of primary aluminum to the main molten pool. After the primary aluminum melts, start the mechanical stirrer and stir at 120 r / min for 8 minutes at 720℃ to homogenize the aluminum liquid. After homogenization, adjust the temperature of the aluminum liquid to 705℃ and use argon gas rotary blowing to degas for 15 minutes. After degassing, let it stand for 20 minutes, skim off the scum on the surface of the aluminum liquid, and then let the aluminum liquid pass through 40ppi and 50ppi ceramic foam filter plates in sequence.

[0045] S6. The filtered molten aluminum is directly cast into a rolled slab at 695℃ using a semi-continuous casting method. After cooling and milling the surface of the rolled slab, it is homogenized at 480℃ for 4 hours. Then, the rolled slab is heated to 470℃ for hot rolling, and the final hot rolling temperature is controlled at 315℃. The hot rolling is carried out to a thickness of 6.0mm. The resulting hot-rolled plate is cold-rolled to a thickness of 1.5mm and then annealed at 360℃ for 2 hours to obtain a low-carbon recycled aluminum alloy plate with a thickness of 1.5mm.

[0046] Example 2

[0047] The difference between this embodiment and embodiment 1 is that the thickness of the aluminum alloy sheet remelting material in S1 is different. Specifically, S1: The aluminum alloy sheet remelting material with a thickness of 1.50mm is cleaned and dried to make its moisture content 0.08% and surface oil content 0.12%, and then preheated at 220℃ for 40 minutes. The remaining steps are the same as in embodiment 1.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that the processing time in S3 is different. Specifically, in S3: the sheet material is assembled into the carrier frame, and then the carrier frame is placed into the carrier aluminum liquid. The circulation pump and mechanical stirrer are kept off, and the process is carried out at 720°C for 20 minutes. The remaining steps are the same as in embodiment 1.

[0050] Example 4

[0051] The difference between this embodiment and Embodiment 1 lies in the amount of aluminum alloy sheet remelting material added in S1. Specifically, S1: 50 portions of aluminum alloy sheet remelting material are sorted, cleaned, dried, and preheated. The preheated aluminum alloy sheet remelting material is divided into 10 batches, with 5 portions in each batch. Each batch of aluminum alloy sheet remelting material is subjected to staggered layering and light compaction to achieve an apparent density of 0.58 g / cm³. 3 The thin sheet material group, the remaining steps are the same as in Example 1.

[0052] Example 5

[0053] The difference between this embodiment and Embodiment 1 is that the Mg mass percentage in the S2 carrier aluminum liquid is 2.5%, while the other steps are the same as in Embodiment 1.

[0054] Example 6

[0055] The difference between this embodiment and Embodiment 1 is that the Mg mass percentage in the S2 carrier aluminum liquid is 3.5%, while the other steps are the same as in Embodiment 1.

[0056] Comparative Example 1 The difference between this comparative example and Example 1 is that, in S3, after the sheet material group is placed into the carrier aluminum liquid, the mechanical stirrer is immediately started so that the sheet material to be returned to the furnace is melted through under forced stirring. The remaining steps are the same as in Example 1.

[0057] Comparative Example 2 Compared with Example 1, the difference in this comparative example is that after the sheet material group completes the melting process in S3-S5 with the circulating pump and mechanical agitator off, the aluminum liquid is mechanically stirred before the residue is removed. After stirring, the residue is removed. The remaining steps are the same as in Example 1.

[0058] Comparative Example 3 The difference between this comparative example and Example 1 is that, after removing the residue of each batch of enriched oxide film in S5, the mechanical stirrer is not started to homogenize the aluminum liquid; the remaining steps are the same as in Example 1.

[0059] Comparative Example 4 The difference between this comparative example and Example 1 is that the mass percentage of Mg in the S2 carrier aluminum liquid is 0.5%, while the other steps are the same as in Example 1.

[0060] Comparative Example 5 The difference between this comparative example and Example 1 is that the mass percentage of Mg in the S2 carrier aluminum liquid is 5.0%, while the other steps are the same as in Example 1.

[0061] To further verify the effects of different treatment methods in the above embodiments and comparative examples on the melting process of the sheet remelting material, the removal state of oxide film residues, and the properties of the resulting molten aluminum and sheet metal, the intermediate products, molten aluminum, and aluminum alloy sheet metal obtained in each embodiment and comparative example were tested and analyzed. Unless otherwise stated, the same sampling location, sampling quantity, and testing method were used in each group, and the test results were taken as the average value of parallel samples. The following experimental examples focus on residue enrichment and removal, melt inclusion control, melt temperature and composition uniformity, internal inclusion state of sheet metal, and forming performance in sequence to illustrate the influence of each operation of the present invention and its order on the technical effect. Three parallel sampling tests were conducted in each group.

[0062] Experimental Example 1 To verify whether the oxide film on the surface of the sheet metal scrap could be retained in the frame and removed along with the residue when the sheet metal scrap was placed in a support frame and melted with the circulating pump and mechanical stirrer off, and to examine whether this treatment method significantly prolonged the melting time and whether excessive metal was entrained during the removal of the residue, experiments were conducted according to the preparation methods of Examples 1-6 and Comparative Examples 1-5. All groups used the same batch of aluminum alloy sheet metal scrap, block aluminum alloy scrap, and primary aluminum, and the total amount of aluminum raw materials remained consistent. Except for the process conditions that were clearly changed in each example and comparative example, the other melting, degassing, filtration, casting, rolling, and annealing conditions remained consistent.

[0063] The penetration time was started when the sheet material group was completely immersed in the carrier aluminum liquid, and the penetration endpoint was defined as the point at which no continuous metal sheet remained in the residue after the carrier frame was removed. The time difference between the penetration endpoint and the starting point of the sheet material group's immersion in the carrier aluminum liquid was recorded as the penetration time for that group. For Comparative Example 1, since the sheet material group was forcibly stirred immediately after immersion, its penetration time was recorded as the time when no continuous metal sheet was observed under forced stirring conditions. For Comparative Example 2, its penetration time was recorded as the time when no continuous metal sheet was observed during the penetration stage with the circulating pump and mechanical stirrer turned off.

[0064] After the melting process is completed and the corresponding residue removal operation is finished, the residue is placed above the main molten pool for draining. The draining time is the same as that in each embodiment or comparative example. After the residue is cooled to room temperature, it is weighed to obtain the mass of the residue after draining. The mass ratio of the residue is calculated according to the following formula: the mass ratio of the residue is equal to the mass of the residue after draining divided by the mass of the sheet remelting material fed into the furnace and then multiplied by 100%.

[0065] To detect recyclable metals entrained in the residue, the weighed residue was crushed to a maximum particle size of no more than 20 mm, mixed evenly, and a representative sample was placed in a graphite crucible and kept at 750℃ for 20 min to allow the aluminum metal entrained in the residue to remelt and coalesce. After cooling, the residue was separated and the mass of the remelted and recovered metal was weighed. The recyclable metal content in the residue was calculated according to the following formula: the recyclable metal content in the residue is equal to the mass of the remelted and recovered metal divided by the mass of the residue after leaching, multiplied by 100%. Each group was tested in parallel for 3 times, and the results are expressed as mean ± standard deviation. The test results are shown in Table 1.

[0066] Table 1. Results of melting process and residue state detection for each preparation method As shown in Table 1, the melting time of Examples 1-6 was 10.9-12.7 min, the mass ratio of residue was 6.4%-7.2%, and the content of recoverable metal in the residue was 10.8-15.0%. It can be seen that when the sheet material is placed in the support frame and melting is carried out with the circulating pump and mechanical agitator off, the metal matrix in the sheet remelting material can be melted out and enter the main melting pool. The residue with enriched oxide film can be concentrated in the support frame and removed. Moreover, the proportion of recoverable metal entrained in the residue is low, and the removal of residue will not cause excessive metal to be carried out.

[0067] In Comparative Example 1, mechanical stirring was started immediately after the thin sheet material was placed into the carrier aluminum liquid. In Comparative Example 2, mechanical stirring was performed before the residue was removed. The mass percentage of residue in both examples was lower than that in Example 1. This indicates that forced stirring before the residue is removed weakens the concentrated retention state of the enriched oxide film residue, reducing the amount of residue that can be concentratedly removed. In Comparative Examples 4 and 5, the mass percentage of Mg in the carrier aluminum liquid was adjusted to 0.5% and 5.0%, respectively, and the mass percentage of residue was 3.5% and 4.1%, respectively. This shows that both too low and too high Mg content in the carrier aluminum liquid are not conducive to the concentrated retention and pre-removal of the enriched oxide film residue. In Comparative Example 3, since the mechanical homogenization step after the residue was removed was eliminated, it did not affect the concentrated formation and removal of residue.

[0068] Experiment Example 2 To verify the effects of the melting penetration method of the sheet material, the timing of residue removal, and the Mg content of the carrier aluminum liquid on the cleanliness of the aluminum liquid before casting, aluminum liquid was prepared according to the preparation methods of Examples 1-6 and Comparative Examples 1-5, respectively. The oxide inclusion area index and hydrogen content of each group of aluminum liquid were tested. The oxide inclusion area index was used to evaluate the amount of oxide inclusions in the aluminum liquid before casting; the hydrogen content was used to evaluate the gas content of each group of aluminum liquid. All groups used the same batch of aluminum alloy sheet remelting material, block aluminum alloy remelting material, and primary aluminum, and the total amount of aluminum raw materials remained consistent. Except for the process conditions that were explicitly changed in each example and comparative example, the other melting, degassing, filtration, and sampling conditions were kept consistent. Each group was sampled after degassing, settling, and filtration were completed according to the corresponding preparation method, and before the aluminum liquid entered the semi-continuous casting. Before sampling, the slag on the surface of the sampling location was removed, the sampling location was the middle of the molten pool, and the sampling depth was kept consistent.

[0069] The oxide inclusion area index was determined using a porous ceramic disc filtration analysis method. During the test, a preheated sampling spoon was used to take a sample from the molten aluminum, with a single sample mass of 1.00 kg. The molten aluminum was then passed through a preheated porous ceramic filter under the same negative pressure conditions. The filter had an average pore size of 20 µm. After filtration, the filter was cooled to room temperature. The area trapped by the filter was then inlaid, ground, and polished. Finally, the non-metallic inclusions in the trapped area were observed and images were acquired using a metallographic microscope and a scanning electron microscope.

[0070] During the statistical analysis, non-metallic inclusions in the image that appear as sheets, films, flocculent masses, or agglomerates were treated as oxide inclusions. At least 20 fields of view were selected for each filter, and the cumulative statistical area was no less than 100 mm². 2 Image analysis software was used to calculate the total projected area of ​​oxide inclusions within the statistical region. The oxide inclusion area index is equal to the total projected area of ​​oxide inclusions within the filter's retention area divided by the mass of molten aluminum passing through the filter. The unit of the oxide inclusion area index is mm. 2 / kg, the larger the value, the more oxide inclusions are trapped in the unit mass of aluminum liquid, and the worse the cleanliness of the aluminum liquid.

[0071] Hydrogen content was detected using an aluminum melt hydrogen analyzer. Before detection, the hydrogen probe and sampling components were preheated and calibrated according to equipment requirements. After calibration, the probe was inserted into the middle of the molten aluminum pool at a consistent depth. The hydrogen content was recorded after the instrument reading stabilized. Each group of aluminum melts was tested three times consecutively, with an interval of no less than 2 minutes between each test. The average of the three test results was taken as the hydrogen content of the group of aluminum melts, in mL / 100gAl. The oxide inclusion area index and hydrogen content of each group were tested three times. The results are expressed as mean ± standard deviation. The test results are shown in Table 2.

[0072] Table 2. Detection results of oxide inclusions and hydrogen content in aluminum melts obtained by various preparation methods. Table 2 shows that the hydrogen content of the aluminum melts in each group ranged from 0.116 to 0.126 mL / 100gAl, with little difference between groups. This result indicates that the differences in the oxide inclusion area index among the groups were not caused by different degassing degrees, but mainly by the melting penetration method of the sheet material, the timing of residue removal, and the Mg content of the carrier aluminum melt. The oxide inclusion area index of the aluminum melts obtained in Examples 1-6 ranged from 0.29 to 0.41 mm. 2 / kg, which is at a relatively low level overall, indicating that the present invention, by placing the sheet material group in a support frame and melting it thoroughly with the circulating pump and mechanical stirrer off, and then removing the residue enriched with oxide film before mechanical homogenization, can reduce oxide inclusions entering the main molten pool and maintain a better clean state of the aluminum liquid before casting. Comparative Examples 1-2 both stirred the aluminum liquid before removing the residue, and the oxide inclusion area index was higher than that of Example 1. Comparative Examples 4 and 5 adjusted the Mg mass percentage content of the carrier aluminum liquid to 0.5% and 5.0% respectively, and their oxide inclusion area indices were 0.83 mm. 2 / kg and 1.05mm 2 / kg, all higher than in Example 1. The results of the above four comparative examples show that too low or too high Mg content in the carrier aluminum liquid and mechanical stirring before removing residues are not conducive to the control of aluminum liquid oxide inclusions.

[0073] Experimental Example 3 To verify the effects of different melting methods, residue removal time points, and Mg content in the carrier aluminum melt on the distribution of oxide inclusions in the finished sheet, 1.5 mm annealed sheets prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to inclusion string detection. Inclusion string refers to a linear inclusion region that is continuously distributed along the rolling direction after the sheet is rolled, or formed by multiple oxide inclusions arranged discontinuously along the rolling direction. The number of inclusion strings is used to evaluate the amount of inclusion defects distributed along the rolling direction in the sheet. The total length of inclusion strings and the maximum length of inclusion strings are used to evaluate the extent of inclusion defect extension. The maximum size of a single inclusion is used to evaluate the size of a larger local inclusion in the sheet.

[0074] All plates were prepared using the same batch of aluminum raw materials. Except for the process conditions that were clearly changed in each example and comparative example, the casting, homogenization treatment, hot rolling, cold rolling and annealing conditions were kept consistent.

[0075] During sampling, samples were taken from the left, middle and right sides of each sheet. When sampling, the observation section was made parallel to the rolling direction and thickness direction of the sheet. After the sample was inlaid, ground and polished, the distribution of inclusions was first observed with a metallographic microscope, and then the morphology of representative inclusions was observed with a scanning electron microscope.

[0076] In this experimental example, a linear defect consisting of two or more inclusions arranged continuously or intermittently along the rolling direction, with the distance between adjacent inclusions not exceeding 50µm, is counted as an inclusion string. Three plates are taken for each group, and 10 fields of view are observed at the three positions mentioned above for each plate. The area is calculated based on 100mm². 2 Conversion; the number of interstitial tandems is calculated based on the number of interstitial tandems per unit statistical area, with the unit being strips / 100mm. 2The average string length is the arithmetic mean of the string lengths of inclusions at each sampling location, and the standard deviation is the standard deviation between the average values ​​at different sampling locations, in mm. The maximum string length of inclusions is the maximum projected length of a single string of inclusions in the statistical field of view, in mm, and is not included in the calculation of the standard deviation of the average string length. The maximum single inclusion size is the maximum length of a single oxide inclusion in the statistical field of view, in µm. The detection results for each group are expressed as mean ± standard deviation. The detection results are shown in Table 3.

[0077] Table 3. Statistical results of inclusion tandem arrangement in the plates obtained by each preparation method. As shown in Table 3, the number of inclusions in the plates obtained in Examples 1-6 is 2.3-3.5 per 100mm. 2 The average string length was 0.15-0.24 mm, the maximum string length was 0.36-0.62 mm, and the maximum inclusion length was 15.8-22.8 µm. These results indicate that placing the sheet material within a support frame and performing melting with the circulating pump and mechanical agitator off, followed by removing the oxide film-enriched residue before mechanical homogenization, can reduce the entry of oxide film into the main molten pool and the formation of inclusion strings extending along the rolling direction during rolling. The resulting sheet has fewer inclusion strings, and both the string length and the length of a single inclusion are within acceptable limits. At a lower level, Comparative Examples 1-2 mechanically stirred the aluminum melt before removing the residue, which broke up the oxide film-enriched residue and allowed it to enter the aluminum melt. As a result, the number and length of the inclusions were higher than those in Examples 1-6. Comparative Examples 4 and 5 adjusted the Mg content of the carrier aluminum melt to 0.5% and 5.0% respectively. As can be seen from Examples 1 and 2, both too low and too high Mg content in the carrier aluminum melt are not conducive to the concentrated retention and pre-removal of the oxide film residue, which ultimately increases and lengthens the inclusions extending along the rolling direction in the plate.

[0078] Experiment Example 4 To verify the bending stability, tensile properties, and width-direction consistency of low-carbon recycled aluminum alloy sheets obtained by different preparation methods, 1.5mm annealed sheets prepared in Examples 1-6 and Comparative Examples 1-5 were subjected to 180° bending tests and tensile property tests. The 180° bending test was mainly used to detect the cracking rate, average number of cracks, and longest crack length in a single piece. The tensile property test mainly tested the tensile strength Rm, the specified plastic extension strength Rp0.2, and the elongation after fracture A50. All sheets were prepared using the same batch of aluminum raw materials. Except for the process conditions that were explicitly changed in the examples and comparative examples, the casting, homogenization treatment, hot rolling, cold rolling, and annealing conditions were kept consistent.

[0079] Cracking rate is used to evaluate the cracking tendency of sheet metal during 180° bending deformation; average number of cracks is used to evaluate the frequency of crack occurrence on the surface of a single bent specimen; longest crack length in a single specimen is used to evaluate the extent of extension of the most severe crack in a single specimen after bending; tensile strength Rm, specified plastic extension strength Rp0.2, and elongation at break A50 are used to evaluate the basic mechanical properties of sheet metal, of which A50 mainly reflects the plastic deformation capacity of sheet metal; Rm width range and A50 width range are used to evaluate the performance consistency of sheet metal in the width direction.

[0080] In the 180° bending test, each group was tested three times, with 30 bending samples taken each time. The samples were taken from annealed 1.5mm thick plates, and the bending axis was perpendicular to the rolling direction. After bending, the outer arc surface of the bending was observed under the same magnification. The number of samples with visible cracks was recorded, and the number of cracks on the outer arc surface of each sample and the longest crack length in a single sample were counted. The bending crack rate was calculated by dividing the number of samples with visible cracks by the total number of bending samples and then multiplying by 100%. The average number of cracks was calculated based on the number of visible cracks on the outer arc surface of each bending sample, in units of cracks / sample. The longest crack length in a single sample was the length of the longest visible crack on the outer arc surface of a single sample in the same group of bending samples, in units of mm. The test results are expressed as the average value ± standard deviation of the three repeated tests. The results are shown in Table 4.

[0081] Table 4. Results of 180° bending tests on the sheets obtained by each preparation method. As shown in Table 4, the sheets obtained in Examples 1, 3, and 4 did not crack during the 180° bending test; the bending cracking rate of Examples 2 and 5 was 3.3%, and the bending cracking rate of Example 6 was 6.7%. Moreover, the average number of cracks in Examples 1-6 did not exceed 0.07 cracks / piece, and the longest crack length in a single piece did not exceed 0.18 mm. These results indicate that placing the sheet material group in the bearing frame and melting it with the circulating pump and mechanical agitator turned off, followed by removing the residue of the enriched oxide film before mechanical homogenization, can reduce the cracking tendency of the finished sheet material during the 180° bending process and maintain good bending forming stability.

[0082] Comparative Examples 1 and 2 were mechanically stirred before the residue was removed. The bending crack rate, average number of cracks, and longest crack length of a single piece of the two groups of plates were all higher than those of Example 1, indicating that mechanical stirring before the residue was removed would reduce the bending stability of the plates. Comparative Examples 4 and 5 had the Mg mass percentage content of the carrier aluminum liquid adjusted to 0.5% and 5.0% respectively. The bending crack rate and crack length were both higher than those of Example 1, indicating that both too low and too high Mg content in the carrier aluminum liquid are detrimental to the bending stability of the plates.

[0083] In the tensile test, all tensile specimens were cut from annealed 1.5mm thick sheet metal. The tensile test was conducted at room temperature. Before the test, the specimens were clamped in the universal testing machine fixture, ensuring that the length direction of the specimen was aligned with the loading direction to avoid skewed force application. During the test, an extensometer was installed in the gauge length section of the specimen to determine the specified plastic extension strength and elongation at break. Initially, a beam displacement speed of 2mm / min was used. Once the specimen exceeded the specified plastic extension strength, the beam displacement speed was adjusted to 10mm / min, and the tensile test continued until fracture. If the specimen fractured at the clamping end, or if the fracture distance from the gauge end was less than 1 / 4 of the gauge length, the result for that specimen was not included in the statistical analysis, and a new specimen was prepared. Take samples and perform tensile tests. Record the specified plastic extension strength, tensile strength, and elongation after fracture for each sample. The specified plastic extension strength is represented by Rp0.2, the tensile strength by Rm, and the elongation after fracture by A50. Calculate the average values ​​of Rp0.2, Rm, and A50 for each group, and calculate the width range of A50. The width range of Rm is the difference between the maximum and minimum average values ​​of Rm for the left, middle, and right sides of the same group of plates. The width range of A50 is the difference between the maximum and minimum average values ​​of A50 for the left, middle, and right sides of the same group of plates. The width range of Rm and A50 are used to evaluate the strength and plasticity of the plates in the width direction, respectively. The specific results are shown in Table 5.

[0084] Table 5. Auxiliary tensile test results of the plates obtained by each preparation method As shown in Table 5, the tensile strength Rm of the plates obtained in Examples 1-6 is 220-223 MPa, the specified plastic elongation strength Rp0.2 is 100-102 MPa, and the elongation after fracture A50 is 23.6%-24.8%. Meanwhile, the width-direction Rm range of Examples 1-6 is 5-7 MPa, and the width-direction A50 range is 1.2%-1.6%. These results indicate that the processing method of the present invention does not reduce the basic strength and plasticity of the plate while controlling the inclusion chain and bending cracks. Furthermore, the mechanical properties of the obtained plates fluctuate less in the width direction. In Comparative Example 3, mechanical homogenization after removing the residue was cancelled, the width-direction Rm range and the width-direction A50 were higher than those in Example 1, indicating that aluminum liquid homogenization is still required after removing the residue to improve the consistency of the plate's performance in the width direction.

[0085] As can be seen from Tables 4 and 5, Examples 1-6 can maintain A50 at a high level while keeping Rm and Rp0.2 stable, and keep the 180° bending crack rate, average number of cracks and longest crack length of a single piece at a low level. Comparative Examples 1 and 2 show that mechanical stirring before removing the residue will significantly reduce the bending stability of the sheet. Comparative Example 3 shows that mechanical homogenization is still required after removing the residue. Comparative Examples 4 and 5 show that both too low and too high Mg content in the carrier aluminum liquid will increase the tendency of the sheet to bend and crack. The process sequence and control of Mg content in the carrier aluminum liquid of the present invention can improve the plasticity and local bending stability of recycled aluminum alloy sheets.

[0086] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.

Claims

1. A method for preparing low-carbon recycled aluminum alloy sheet, characterized in that, Includes the following steps: S1: The sheet or strip remelting material with a thickness of 0.20-2.00mm produced by cutting, slitting, punching or cutting aluminum alloy sheets and strips is cleaned and dried until the moisture content is not higher than 0.20% and the surface oil content is not higher than 0.30%, and then stacked into thin sheet groups with connecting gaps between the sheets for the carrier aluminum liquid to enter and the liquid metal to flow out. S2: A carrier aluminum liquid is formed in the smelting furnace. The Mg mass percentage in the carrier aluminum liquid is 2.5%-3.5%. Forced circulation and mechanical stirring are stopped before the carrier aluminum liquid is added to the sheet material group. S3: The sheet material group is placed in the aluminum molten aluminum carrier frame and immersed in the carrier aluminum molten aluminum. The carrier frame is provided with liquid permeation openings on the side and bottom to allow the carrier aluminum molten aluminum to enter and the molten metal to flow out. The metal matrix is ​​melted under the state of forced circulation and mechanical stirring stopped. The liquid metal enters the main molten pool through the connecting gap and liquid permeation opening. The enriched oxide film residue in the form of flakes, films, flocculents or agglomerates is left in the carrier frame. S4: Before starting forced circulation or mechanical stirring, remove the support frame along with the residue of the enriched oxide film from the molten aluminum; S5: After the residue of the enriched oxide film is removed, start forced circulation or mechanical stirring to homogenize the aluminum liquid in the main molten pool, and adjust the composition, degas and filter the aluminum liquid to obtain purified aluminum liquid. S6: The purified aluminum liquid is cast into rolled slabs in the same furnace. The rolled slabs are then homogenized, hot-rolled, cold-rolled and annealed to obtain low-carbon recycled aluminum alloy sheets.

2. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In S1, the sheet material group is formed by interleaving and compacting recycled aluminum alloy sheets, and the apparent density of the sheet material group is 0.35-0.90 g / cm³. 3 Furthermore, gaps are maintained between the thin sheets to allow for interconnection.

3. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In S1, the cleaned and dried aluminum alloy sheet remelting material is preheated at 150-300℃ for 20-60 minutes, and then the preheated aluminum alloy sheet remelting material is stacked to form the sheet material group.

4. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In step S2, the carrier aluminum liquid is formed by melting block aluminum alloy recycled material and / or primary aluminum in a smelting furnace. The block aluminum alloy recycled material and the low-carbon recycled aluminum alloy sheet to be prepared belong to the same aluminum alloy series.

5. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In S3, the sheet material is immersed in the carrier aluminum liquid in batches. The mass of each batch of aluminum alloy sheet remelting material is 5%-15% of the total mass of aluminum raw materials used to prepare the low carbon recycled aluminum alloy sheet. The sheet material is treated in the carrier aluminum liquid at a temperature of 700-735℃ for 8-25 minutes. During the treatment, the carrier frame is not subjected to reciprocating impact or flipping.

6. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In S4, after each batch of sheet material is fully melted, the carrier frame along with the residue of the enriched oxide film is moved to the top of the main melting pool for 2-8 minutes to drain.

7. The method for preparing low-carbon recycled aluminum alloy sheet according to claim 1, characterized in that, In S5, after all batches of enriched oxide film residues have been removed, the main molten aluminum pool is mechanically stirred and homogenized at 700-730℃, with a stirring speed of 60-180 r / min and a homogenization time of 3-15 min.

Citation Information

Patent Citations

  • Low-temperature immersed melting process method for secondary aluminum

    CN102140579B

  • A 5XXX aluminum alloy and its preparation method and application

    CN118957369B

  • Low-temperature immersed melting process method for secondary aluminum

    CN102140579A

  • Aluminum alloy cast ingot added with high-proportion aluminum scrap, preparation method of aluminum alloy cast ingot and aluminum alloy plate strip

    CN117737481A